Management Equity: Parish Administration and Pastoral Leadership - Anduyan, Dennis B.; Celis, Rev. Fr. Arnel D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The thin line between management from leadership inside an organization is something that many people in positions of power constantly face and experience. Leaders usually take on administrative obligations and carry out a number of administrative duties. On the other hand, leadership and administration are two unique, but complimentary, systems of activity. This study aimed to determine the level of Parish administration and Pastoral leadership of the clergy in the Diocese of Tagum. Findings of the study will serve as basis for the diocesan organizational development interventions program. The study utilized descriptive-correlational design as well as comparative design. The study was conducted among the ten parishes under the Diocese of Tagum for CY 2014. There were 593 respondents of the study comprising the clergy, parishioners, parish workers and apostolate. It employed a research instrument based on the framework of McKinsey’s 7S. The study employed frequency and percentage, pearson-r correlation and one-way analysis of variance to treat the data. Parish administration is very satisfactory. The vision and mission is also very satisfactory. The level of pastoral leadership is very satisfactory. There is interaction effectively with people, balancing positive regard for self with positive regard for others and working harmoniously with peers, superiors, and subordinates in the workplace, which is very satisfactory. It is concluded that there is a significant relationship between parish administration and pastoral leadership. Also, there is a significant difference on pastoral leadership across clergymen. Parish administration has a significant effect on pastoral leadership. This means that improving parish administration improves the pastoral leadership.